Numerical analysis of the dynamic frequency responses of damaged micro-lattice core sandwich plates - Braun, Matías (2019)
In this work, a numerical analysis of the dynamic frequency responses of sandwich plates with micro-lattice core is presented. The finite element analysis is implemented in the commercial software Abaqus/Standard, calculating the natural frequencies and eigenmodes of sandwich plates containing defects on the micro-lattice structure. In order to include the presence of defects, an aleatory algorithm is developed in MATLAB. The effect of the damage percentage, cell type, cell size and material on the frequency and modal responses of the sandwich plates is highlighted. Results show that the dynamic frequency response may be useful for analysing practical issues related to non-destructive damage identification of imperfections in the micro-lattice core of sandwich structures.